To “see” what the city hall does: public communication on Florianópolis city hall’s Instagram - Comel, Naiza; Moura, Júlia Frank de (Organicom, 2023)
This article analyzes how the city hall of Florianópolis uses Instagram as a public communication tool. To that end, a content analysis of 66 posts published between January and July 2022 was carried out. The results indicate that the tone of the posts is mostly informative and the most recurrent types of posts are those of services and guidelines – which demonstrates the preoccupation of the city hall with normative public communication. Among the themes, health, culture, and tourism stand out.